ISRIA statement: ten-point guidelines for an effective process of research impact assessment - Paula Adam; Pavel V. Ovseiko; Jonathan Grant; Kathryn E. A. Graham; Omar F. Boukhris; Anne-Maree Dowd; Gert V. Balling; Rikke N. Christensen; Alexandra Pollitt; Mark Taylor; Omar Sued; Saba Hinrichs-Krapels; et al. (Health Research Policy and Systems, 2018)
Abstract As governments, funding agencies and research organisations worldwide seek to maximise both the financial and non-financial returns on investment in research, the way the research process is organised and funded is becoming increasingly under scrutiny. There are growing demands and aspirations to measure research impact (beyond academic publications), to understand how science works, and to optimise its societal and economic impact. In response, a multidisciplinary practice called research impact assessment is rapidly developing. Given that the practice is still in its formative stage, systematised recommendations or accepted standards for practitioners (such as funders and those responsible for managing research projects) across countries or disciplines to guide research impact assessment are not yet available. In this statement, we propose initial guidelines for a rigorous and effective process of research impact assessment applicable to all research disciplines and oriented towards practice. This statement systematises expert knowledge and practitioner experience from designing and delivering the International School on Research Impact Assessment (ISRIA). It brings together insights from over 450 experts and practitioners from 34 countries, who participated in the school during its 5-year run (from 2013 to 2017) and shares a set of core values from the school’s learning programme. These insights are distilled into ten-point guidelines, which relate to (1) context, (2) purpose, (3) stakeholders’ needs, (4) stakeholder engagement, (5) conceptual frameworks, (6) methods and data sources, (7) indicators and metrics, (8) ethics and conflicts of interest, (9) communication, and (10) community of practice. The guidelines can help practitioners improve and standardise the process of research impact assessment, but they are by no means exhaustive and require evaluation and continuous improvement. The prima facie effectiveness of the guidelines is based on the systematised expert and practitioner knowledge of the school’s faculty and participants derived from their practical experience and research evidence. The current knowledge base has gaps in terms of the geographical and scientific discipline as well as stakeholder coverage and representation. The guidelines can be further strengthened through evaluation and continuous improvement by the global research impact assessment community.